Suppression of the antiviral response by an influenza histone mimic - Marazzi, Ivan; Ho, Jessica S. Y.; Kim, Jaehoon; Manicassamy, Balaji; Dewell, Scott; Albrecht, Randy A.; Seibert, Chris W.; Schaefer, Uwe; Jeffrey, Kate L.; Prinjha, Rab K.; Lee, Kevin; García-Sastre, Adolfo; et al. (Nature (London), 2012)
Viral infection is commonly associated with virus-driven hijacking of host proteins. Here we describe a novel mechanism by which influenza virus affects host cells through the interaction of influenza non-structural protein 1 (NS1) with the infected cell epigenome. We show that the NS1 protein of influenza A H3N2 subtype possesses a histone-like sequence (histone mimic) that is used by the virus to target the human PAF1 transcription elongation complex (hPAF1C). We demonstrate that binding of NS1 to hPAF1C depends on the NS1 histone mimic and results in suppression of hPAF1C-mediated transcriptional elongation. Furthermore, human PAF1 has a crucial role in the antiviral response. Loss of hPAF1C binding by NS1 attenuates influenza infection, whereas hPAF1C deficiency reduces antiviral gene expression and renders cells more susceptible to viruses. We propose that the histone mimic in NS1 enables the influenza virus to affect inducible gene expression selectively, thus contributing to suppression of the antiviral response. The H3N2 influenza virus immunomodulatory protein NS1 carries a sequence that mimics the histone H3 tail; this sequence interferes with the host antiviral response via binding to the cellular regulator of RNA elongation, hPAF1C. Flu-virus mimicry Histone proteins are essential regulators of gene function. The amino-terminal domain of the histone H2, or the histone 'tail', can be post-translationally modified, and it acts as a scaffold for the assembly of protein complexes that control gene function. Ivan Marazzi and colleagues now show that the immunosuppressive NS1 protein of the influenza virus carries a histone-like sequence that mimics key features of histone H3, including binding to key transcriptional regulators, so that the virus can hijack the host transcriptional machinery. Interaction between NS1 and transcriptional elongation complex PAF1C is shown to be crucial to the host antiviral response, validating PAF1 protein as a candidate for anti-inflammatory therapy using synthetic PAF1 antagonists.